2021
DOI: 10.14202/vetworld.2021.1020-1027
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic resistance of Escherichia coli and Salmonella spp. strains isolated from healthy poultry farms in the districts of Abidjan and Agnibilékrou (Côte d'Ivoire)

Abstract: Background and Aim: Antimicrobial resistance (AMR) is a serious challenge to animal and human health worldwide. Therefore, this study aims to determine levels and patterns of AMR of Escherichia coli and Salmonella spp. strains isolated from poultry farms in Côte d'Ivoire. Materials and Methods: A cross-sectional study was conducted in two districts of Côte d'Ivoire with high poultry production: Abidjan and Agnibilékrou. A total of 231 fecal samples were collected in 124 poultry farms in both districts. Entero… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
5
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 36 publications
4
5
1
Order By: Relevance
“…The results revealed that multidrug resistance was observed in all Salmonella isolates against four antibiotics or more and in all E. coli isolates against three antibiotics or more (except in O44). This high prevalence of multidrug resistance in Salmonella and E. coli has been previously reported in Egypt (Amer et al, 2018), Bangladesh (Matin et al, 2017), Pakistan (Kamboh et al, 2018), western Algeria (Yahya et al, 2021) and in Côte d'Ivoire (Assoumy et al, 2021).…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…The results revealed that multidrug resistance was observed in all Salmonella isolates against four antibiotics or more and in all E. coli isolates against three antibiotics or more (except in O44). This high prevalence of multidrug resistance in Salmonella and E. coli has been previously reported in Egypt (Amer et al, 2018), Bangladesh (Matin et al, 2017), Pakistan (Kamboh et al, 2018), western Algeria (Yahya et al, 2021) and in Côte d'Ivoire (Assoumy et al, 2021).…”
Section: Discussionsupporting
confidence: 68%
“…Moreover, Salmonella species showed 85.7% resistance against flumequine. In previous studies, this high Salmonella resistance was reported against the same antibiotics in Egypt (Al-baqir et al, 2019), India (Waghamare et al, 2018), Pakistan (Kamboh et al, 2018), Bangladesh (Parvin et al, 2020), western Algeria (Yahya et al, 2021) and Côte d'Ivoire (Assoumy et al, 2021).…”
Section: Discussionmentioning
confidence: 66%
“…A lower MDR of 52.3% compared to our study was reported previously [67]. High-level resistance has also been documented [56,68,69]. This poses a severe public health threat due to the resistance to a broad range of antibiotics observed in this study and could be a consequence of continuous exposure and extensive usage of these antibiotics in these study areas [27].…”
Section: Plos Onesupporting
confidence: 41%
“…These results are consistent with a study conducted in Bangladesh in 2014, which recorded a prevalence of 87.55% for Escherichia Coli and 66.66% for Salmonella spp, although this was done on litter samples rather than directly in the intestines, increasing the risk of environmental contamination [10]. Similar observations were made in Côte d'Ivoire in 2021, where a high percentage of Escherichia Coli isolates, 91.74%, was observed, but with a lower prevalence of 15.58% for Salmonella spp [11]. In contrast, relatively lower results were reported in Thailand in 2021, with only 33.33% of samples containing Escherichia Coli and 33.34% containing Salmonella spp [12].…”
Section: Discussionmentioning
confidence: 77%